Effects of Intravitreal Aflibercept in Patients with Central Serous Chorioretinopathy: Doi:10.36351/pjo.v36i4.1098 - Bodla, Ali Afzal; Afzal Bodla, Muhammad; Minahil Kazmi, Syeda; Moazzam, Ayema (Pakistan Journal of Ophthalmology, 2020)
Purpose: The purpose of this study is to assess the efficacy of intravitreal injection of Afliberceptin patients with chronic central serous chorioretinopathy (CSCR). Study Design: Interventional case series. Place and Duration of Study: Multan Medical and Dental Centre and Bodla Eye Care from February 2019 to February 2020. Methods: This study was conducted on fifteen eyes with sub-acute to chronic central serous chorioretinopathy. All patients who had undergone previous treatment with laser photocoagulation, intravitreal triamcinolone, or bevacizumab in past 3 months, history of glaucoma (intraocular pressure > 21 mmHg), patients who lost to follow-up, and those with previously vitrectomized eyes were excluded. Patients were treated with a single dose of intravitreal injection of Aflibercept (0.5 mg/0.05 ml). Visual acuity with Log MAR chart and central retinal thickness were studied before and after the injection. Results: The mean age of the patients was 30.46 years ± 9 years. After one month of intravitreal Aflibercept injection, visual acuity improved from 0.32 Log MAR to 0.173 log MAR and at 3 months (the last follow-up) it was 0.206 Log MAR. Central retinal thickness (CRT) improved from 437 ± 82 µm (at the time of presentation) to 349 ± 67 µm at 1 month post injection. At the last follow-up the mean CRT decreased to 309 ± 121 µm. Except for two eyes, all eyes showed visual improvement. These two eyes had a higher CRT as compared to other participants. Conclusion: Intravitreal injection of Afliberceptis effective in improving BCVA and decreasing the central retinal thickness in patients central serous chorioretinopathy. Key Words: Central retinal thickness, Central Serous chorioretinopathy, Aflibercept.